2000
DOI: 10.1107/s0021889899015575
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of X-ray diffraction profiles by using series expansion

Abstract: The deconvolution of X‐ray diffraction profiles is a basic step in order to obtain reliable results on the microstructure of crystalline powder (crystallite size, lattice microstrain, etc.). A procedure for unfolding the linear integral equation h = g f involved in the kinematical theory of X‐ray diffraction is proposed. This technique is based on the series expansion of the `pure' profile, f. The method has been tested with a simulated instrument‐broadened profile overlaid with random noise by using Hermite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Minimization problems of the form (2) can be found in the signal deconvolution literature and elsewhere: some examples include super-resolution in imaging [6], entropy estimation for discrete distributions [7], X-ray diffraction [8], and neural spike sorting [3]. Here, P θ (w) is a convex penalty function of (θ, w).…”
Section: Model Fitting -Existing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimization problems of the form (2) can be found in the signal deconvolution literature and elsewhere: some examples include super-resolution in imaging [6], entropy estimation for discrete distributions [7], X-ray diffraction [8], and neural spike sorting [3]. Here, P θ (w) is a convex penalty function of (θ, w).…”
Section: Model Fitting -Existing Approachesmentioning
confidence: 99%
“…Run main loop 5. Return β, the solution to the least-squares problem(8) Main Loop While max(w) > :2. Letting j be the smallest index such that w j = max(w), set S ← S ∪ {j} 3.…”
mentioning
confidence: 99%
“…The use of deconvolution techniques of X-ray diffraction (XRD) pattern has been subjected to widespread investigation and is well documented in the literature [1][2][3]. Song et al [4] reported that the deconvoluted sample diffraction intensity improved by exact sampling of diffraction intensity.…”
Section: Introductionmentioning
confidence: 99%